Peningkatan Keaktifan dan Hasil Belajar IPA melalui Media Video Kelas VIII SMP Negeri 07 Bengkulu Tengah - Dwi Anggriyani (Publikasi Indonesia, 2022)
Learning during the pandemic that was applied at SMP Negeri 07 Bengkulu Tengah was good in terms of online via google forms and offline assignments via WA groups experienced problems, especially in terms of low student activity and learning outcomes. This study aims to increase the activeness and learning outcomes of science through video media for class VIII SMP Negeri 07 Bengkulu Tengah. This research is a classroom action research with two cycles in class VIII SMP Negeri 07 Bengkulu Tengah. Methods of data collection by tests, observations, and documentation. Data were analyzed by quantitative and qualitative descriptive. The results of the study concluded that there was an increase in activeness and learning outcomes in science through video media for class VIII SMP Negeri 07 Bengkulu Tengah. This can be seen from the increase in student activity on the indicators of asking and answering questions as well as the average student learning outcomes which always increase. Cycle I the average student learning outcomes are 63.88 or an increase of 23.80% with the percentage of student learning completeness of 0.23 or an increase of 23.80%. In the second cycle, the average score of 77.85 students increased by 57.15% with the percentage of student learning completeness of 0.81 or an increase of 58%.